Redesain Antarmuka Pengguna Website Unitrend Menggunakan Metode Lean UX dan Design Thinking - Muhamad Ihsan Nuril Anwar; Margareta Hardiyanti (Journal of Internet and Software Engineering, 2025)
– In today's digital era, the effectiveness of user interface (UI) design is key to the success of a digital platform, as it can increase user engagement, loyalty, and support institutional goals. By contrast, a lack of UI can cause frustration and reduce the effectiveness of information delivery. Unitrend is a data platform developed by the Institute for Policy Development (PolDev) at Universitas Gadjah Mada, which aims to present and analyze issues in Indonesia, including social, economic, and political issues. However, the initial design of Unitrend faced issues of accessibility and ease of use, which in turn affected the effectiveness of the platform. This research aims to respond to these issues by redesigning the UI using two complementary methods. Lean UX focuses on team collaboration and rapid iteration, while Design Thinking focuses more on empathy and deep understanding of user needs. Test results showed significant improvements in usability. The redesign with Lean UX achieved a success rate of 97.61%, while Design Thinking gave the highest result with a success rate of 99.52% and better time-based efficiency. Based on the User Experience Questionnaire (UEQ) results, both methods showed improvement in all categories, with Design Thinking results proving higher. Although both approaches significantly improve the quality of user experience, Design Thinking is considered more optimal in improving user effectiveness and satisfaction. The findings are expected to provide concrete solutions to improve Unitrend’s UI design quality. Additionally, this study aims to contribute to the development of UI design guidelines for similar digital platforms, enhance information delivery, and enrich the literature on applying both methods in UI redesign